Social skills of elementary school-aged children in urban areas: A sample in Bandung-Indonesia - Fauzi, Irfan; Wirachman, Rony; Arisetyawan, Andika; Yustiana, Yusi Riksa; Kusumawati, Dian (Edelweiss Applied Science and Technology, 2025)
This study aims to evaluate social skills in elementary school-age children. This research was conducted using a survey method of 507 elementary school-age children in urban areas (Bandung-Indonesia). This study uses a social skills rating scale with its aspect referring to the theory of Gresham and Elliott [1] which consists of 5 aspects (cooperation, assertiveness, responsibility, empathy, and self-control). Data analysis in this study uses descriptive statistics to calculate the percentage of social skills. The results of this study show that the social skills of elementary school-age children in Bandung are in the category of fairly good with an average of 3,25 or 81,21%. This shows that elementary school students in Bandung can interact well but sometimes need further support and guidance. The aspect with the highest achievement was empathy, with an average of 3,37 or 84,19% (good), and the aspect with the lowest achievement was self-control, with an average of 3,06 or 76,50% (fairly good). Then, other aspects are cooperation (3,25 or 81,18%), assertiveness (3,24 or 81,02%), and responsibility (3,33 or 83,18%). This research is an important picture related to social skills in elementary school children in urban areas (Bandung-Indonesia), and this is the basis for designing appropriate interventions for social skills development in elementary school children.